2022
DOI: 10.1111/cas.15378
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis is induced by lenvatinib through fibroblast growth factor receptor‐4 inhibition in hepatocellular carcinoma

Abstract: The tyrosine kinase inhibitor lenvatinib is used to treat advanced hepatocellular carcinoma (HCC). Ferroptosis is a type of cell death characterized by the iron‐dependent accumulation of lethal lipid reactive oxygen species (ROS). Nuclear factor erythroid‐derived 2‐like 2 (Nrf2) protects HCC cells against ferroptosis. However, the mechanism of lenvatinib‐induced cytotoxicity and the relationships between lenvatinib resistance and Nrf2 are unclear. Thus, we investigated the relationship between lenvatinib and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…After PD-1 inhibitors therapy, the expression of VEGF and FGF in patients with PD was significantly higher than that of SD patients ( 30 ). Lenvatinib inhibited these angiogenic growth factors and was associated with T-cell activation, enhanced the antitumor immunity, and increased the efficacy of PD-1 inhibitors ( 54 , 55 , 74 ). Additionally, the JAK/STAT3 signaling pathway was activated by FGFR2 signals accompanied with increasing PD-L1 expression according to Li et al.…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
“…After PD-1 inhibitors therapy, the expression of VEGF and FGF in patients with PD was significantly higher than that of SD patients ( 30 ). Lenvatinib inhibited these angiogenic growth factors and was associated with T-cell activation, enhanced the antitumor immunity, and increased the efficacy of PD-1 inhibitors ( 54 , 55 , 74 ). Additionally, the JAK/STAT3 signaling pathway was activated by FGFR2 signals accompanied with increasing PD-L1 expression according to Li et al.…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
“…Inhibition of SLC7A11 by sulfasalazine increases ROS levels and suppresses HCC tumor growth [ 43 ]. Recently, Iseda et al reported that lenvatinib, which is another multiple tyrosine kinase inhibitor (TKI) and first-line treatment for HCC, downregulated the expression of SLC7A11 and induced ferroptosis in HCC cells [ 44 ]. The findings described above indicate that HCC cells may be susceptible to ferroptotic cell death triggered by the suppression of SLC7A11, the expression of which was correlated with poorer survival of HCC patients ( Supplementary Figure S3B ).…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting observation considering that peroxidation of membrane lipids may play a significant role in the mechanism of anticancer action of both drugs. According to the recent studies sorafenib and lenvatinib are also potent inducers of ferroptosis [ 15 , 22 ]—an iron-dependent form of programmed cell death. In case of HCC, ferroptosis is postulated to be one of the main mechanisms responsible for anticancer action of these drugs [ 15 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%